Application of agent-based modeling and simulation to understanding complex management problems in CEM research - Son, Jeongwook; Rojas, Eddy M.; Shin, Seung-Woo (Journal of Civil Engineering and Management, 2015)
As construction projects have become larger and more complex, they develop different features than smaller or traditional projects, which characterize them as complex systems. Still, Construction Engineering and Management (CEM) researchers have mostly relied on traditional approaches to investigate complex management problems, which might produce misleading results. This paper introduces Agent-Based Modeling and Simulation (ABMS) as a research method, and addresses how it could be applied to CEM research. With an illustrative example of the application of ABMS to CEM research, the theoretical background as well as the design, development, and test processes of ABMS are presented. We then made a recommendation on the promising research subjects in CEM area to which ABMS could be suitably applied.